Famílias e diversidade de gênero: um estudo do desempenho das companhias listadas na bolsa de valores brasileira - Valcanover, Vanessa Martins (2019)
Corporate Governance is a relevant issue in Finance, for proposing practices that can mitigate the agency problem, caused by the separation between ownership and control in companies. However, family-based firms do not present such a clear separation, and the existing family relationships can make the agency conflicts more complicated to solve. In the succession process of these companies, it is perceived that females face difficulties to be inserted. However, the participation of women in organizations in general has proved to be important, once it can be a way to mitigate agency conflicts. Thus, it was sought to verify the influence of family structure and gender diversity on the performance of companies listed on the Brazilian stock exchange. Also, it was sought to verify if monitoring and duality affected the performance of family firms, and if the family connections between female directors and executives with their colleagues impacted on the performance of companies. It was used secondary data from the Securities and Exchange Commission and from Economatica, from 2010 to 2017, as well as quantitative techniques for analysis, such as panel data and the generalized method of moments. Through the results, it was verified that, from the 228 firms on the sample, 112 where classified as family firms, and less than 8% of the total seats of the board of directors and of the management teams on the sample were occupied by females. Concerning the impact of family participation on family firms, the results were diverse, showing that a greater number of founders and descendants on the boards leads to a reduction on performance, while the participation of founders and descendants as CEOs or as shareholders affected both positively and negatively, depending on the dependent variable analyzed. Regarding the stock ownership by families, both directly and indirectly, it was perceived a positive effect, confirming the idea that shareholder families tend to watch over their business, leading to a better performance. Concerning the monitoring effect on family firms, the presence of independent directors affected ambiguously the performance, while the size of the boards had a negative effect. Moreover, duality had a positive effect on the performance of family firms. In relation to gender diversity, whose impact was analyzed for the whole sample, it was confirmed that a greater female participation on the boards of directors and on the management teams leads to an increase on the performance of the studied firms. However, the effect of the participation of female directors and executives which exhibited family connection whit their colleagues, was negative, leading to discussions. This research was distinguished by working with a series of variables little studied in Brazil, besides using a fresh database and a relatively recent method. In addition, it allowed to show that, even with the evolution of the composition of firms, many of them still familiar, and brought to light the small number of women working in the companies, giving scope for actions that aim to reduce this gender inequality.